Pengembangan Back-End Ekosistem Digital Ihya Pada Modul Crowdfunding Dengan Metode Iterative Incremental - Rivero Novelino; Rahmat Fauzi; Sinung Suakanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The current economic growth in Indonesia is clearly closely related to the development of the digital era which is always evolving and transforming. Technological developments have not gone unnoticed, especially the economy and the increasing number of applications during the pandemic. Poverty rates and rates of increase are also increasing. One solution in today's digital era is the digital ecosystem. Digital ecosystems can help the process of exchanging information that is integrated with each other and contains various platforms in one container. In the survey of the need for the application of a digital ecosystem, 55.3% answered the need for a digital ecosystem, and the crowdfunding platform was the most preferred choice by 59.6% of respondents. There are many generous people who have more sustenance and want to help others in need, but are afraid to donate and meet in person, so an online crowdfunding platform is needed in this digital ecosystem called Ihya. This crowdfunding platform helps donors who want to donate, as well as fundraisers who need help and want to raise money. Back-end website development using Laravel with iterative incremental method. At the end of the development of the crowdfunding website platform, testing is carried out using black-box testing, namely scenario testing, as well as load testing, and user acceptance tests. The results of the user acceptance test that get a value of 88.8% which shows the user has felt helped by the features that have been made.